Cooling of dam concrete mixes with liquid nitrogen - Nakahara, Yasushi (KICT report (Kajima Institute of Construction Technology), 1988)
"Recently, precooling concrete with liquid nitrogen (LN2) has been attracting attention as a measure to control cracks due to temperature changes in concrete structures. This paper discusses the applicability of precooling dam concrete with LN2 based on the results of on-site tests."